Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fonc.2022.1023776
|View full text |Cite
|
Sign up to set email alerts
|

WDR5 is a prognostic biomarker of brain metastasis from non-small cell lung cancer

Abstract: BackgroundLung cancer (LC) is the most frequent caner type and causes the most cancer-related death. Brain metastases (BM) are the deadliest complications of lung cancer, and the prognostic biomarkers of BM are urgently needed.Materials and methodsIn our study, we established an inception cohort including 122 patients with asynchronous BM from NSCLC, and further selected 70 patients who received surgical resection, which compromised the validation cohort. With immunohistochemistry, we investigated the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Probably, an explanation regarding this intolerance with a clinical point of view could help the readers better understandi, such as the detection of related markers during the treatment or when the intolerance symptoms started to become observable. 4,5 Even though the toxicity mentioned here was only shown by two patients in this study, this issue still could also be proposed for a further study. In addition, the typical toxicities, explained as treatment-related adverse events, were listed without detailed information of each point, such as the liver, kidney, and thyroid function.…”
mentioning
confidence: 74%
“…Probably, an explanation regarding this intolerance with a clinical point of view could help the readers better understandi, such as the detection of related markers during the treatment or when the intolerance symptoms started to become observable. 4,5 Even though the toxicity mentioned here was only shown by two patients in this study, this issue still could also be proposed for a further study. In addition, the typical toxicities, explained as treatment-related adverse events, were listed without detailed information of each point, such as the liver, kidney, and thyroid function.…”
mentioning
confidence: 74%
“…Among these proteins, WD repeat-containing protein 5 (WDR5) attracted our attention, which was a key component of histone H3K4 methyltransferase complex, and could catalyze H3K4me3 [ 24 ]. It is well-known that H3K4me3 is associated with the transcriptional activation of target genes [ 25 ]. Moreover, previous study demonstrated that WDR5 served as a tumor-promoter in NB and high level of WDR5 was positively correlated with poor prognosis of NB patients [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Treatment to patients with BM from NSCLC has not got total consensus ( 25 ). The treatments depend on the performance status, the effect of other adjuvant therapy and overall health of the patient ( 18 ). Many conflicts exist as to the treatment options and the large-scale and multi-centered cohort study should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…CCKAR expression in NSCLC and BM was detected and semi-qualified with IHC by streptavidin peroxidase complex method as previous described ( 18 ). Slides were treated with boiled citrate buffer (pH = 6.0) for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%